Effectiveness and Safety Analysis of PIs/r Based Dual Therapy in Treatment-Naïve, HIV/AIDS Patients: A Network Meta Analysis of Randomized Controlled Trials - Hui, Liu; Xiaoxu, Han; Yuqi, Wang; Peng, Wang; Xin, Wang; Yunyun, Yi; Xin, Li (Frontiers in Pharmacology, 2022)
Background: Dual anti-retroviral therapy is the main proven valuable intervention type for treating naïve HIV/AIDS. Currently, no high-quality evidence is available regarding the best dual schemes. Objectives: The aim of this study is to evaluate the effectiveness and safety of PIs/r-based dual therapy in treatment-naïve HIV/AIDS patients by using network meta-analysis. Methods: Randomized controlled trials of PIs/r-based dual therapy in treatment-naïve HIV/AIDS were searched based on Embase, PubMed and Cochrane library database from January 2006 to June 2021. Taking viral suppression rate, CD4+T cell count changes from baseline as the primary indicator and adverse events rate as secondary indicator, the network meta-analysis was performed on Review Manager and STATA software. Heterogeneity was assessed by the Q statistic and I². We registered our protocol in Prospero with ID CRD42021275466. Results: Among 15 randomized controlled trials (3497 patients and 7 PIs/r-based dual therapy) were reviewed in this study. According to the forest map, DRV/r + INSTIs was more effective compared to triple therapy (TT) in viral suppression (OR 0.82, 95%CI [0.61 - 1.11]), in CD4+T cell count changes from baseline (MD 1.9, 95%CI [0.7, 3.1], I2 86%), in adverse events (OR 0.98, 95%CI [0.68 - 1.39]). Furthermore, SUCRA ranking analysis indicated that DRV/r + INSTIs was superior to TT in viral suppression (DRV/r + INSTIs 75.5% > TT 41.2%) and in immune construction (DRV/r + INSTIs 67% > TT 42%). In addition, DRV/r + INSTIs was similar to TT in adverse events (DRV/r + INSTIs 54.9% ≈ TT 54.7%). Conclusion: DRV/r + INSTIs was obviously superior to TT in viral suppression and immune reconstruction, and was not higher than TT in adverse events.